Gradients in fracture force and grazing resistance across canopy layers in seven tropical grass species. (14th August 2012) - Jacobs, A. A. A.; Scheper, J. A.; Benvenutti, M. A.; Gordon, I. J.; Poppi, D. P.; Elgersma, A.
Abstract In reproductive swards, stems can act as a barrier that affects the grazing behaviour of ruminant livestock. The barrier effect of stems is closely associated with both the force required to fracture the stems and the density of these stems (in combination, these make up grazing resistance), and these factors need to be considered when making predictions about the forage intake of ruminants grazing reproductive pastures. Differences in grazing resistance between sward canopy layers of different grass species are thought to affect bite dimensions, but data are scarce. In this study, we assessed the grazing resistance for three canopy layers of seven tropical grass species. Species differed significantly in grazing resistance for every canopy layer, with a general ranking order for grazing resistance, in ascending order: Cenchrus ciliaris ('American' buffel), Digitaria milanjiana ('Jarra' finger grass), Setaria surgens (annual pigeon grass), Setaria sphacelata ('Narok' setaria), Dichanthium sericeum (Queensland bluegrass), Chloris gayana ('Callide' Rhodes grass). In the top canopy layer, grazing resistance did not appear to create a barrier for any of the species, but in the bottom canopy layer, it did for all species. Species also differed in the relative contribution of fracture force and density to grazing resistance. The results highlight the importance of managing the grazing systems to minimize the barrier effect of the stems, which can be done by controlling the phenological stage of the pasture and the grass species and animal size used in the system.